Urban Water-Related Problems - Kawamura, Akira; Nakagawa, Kei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on urban water-related problems, particularly flash floods and inundation, surface and groundwater pollution, and water shortages, within a broad spectrum of urban water-related challenges. In this reprint, the main target country of those problems is Japan, but other countries including Sweden, Bangladesh, the Philippines, Vietnam, and Thailand are also included. All four review papers and three research articles included in this reprint deal with problems associated with flash flood phenomena from very different aspects of the phenomena. Additionally, five research articles delve into water quality issues concerning both surface and groundwater, while one article addresses water resource concerns.